Economic analysis of Moroccan sheep breeds’ conservation - Lionboui H.; Elame F.; Ouhrouch A.; Benjelloun B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
As in many countries, animal production in Morocco has an important economic, social and nutritional role. However, the conservation of animal genetic resources is still carried out by in situ methods. In order to optimize the sustainable management of animal genetic resources, the economic assessment of animal genetic biodiversity is important. In this case study, we compared the economic value of the main animal breeds In Morocco. Animal breeds selected are prominent in the country, in particular, Beni Guil, Ouled Jellal, Sardi, Timahdit and Dman. Data collection of production costs and sale prices was carried out among farmers and organizations working in the sheep farming sector in Morocco. An economic weighting analysis was implemented in which the marginal profit of breeds was assessed. The economic importance of a character can be expressed by the marginal profit, which results from the increase of a unit of this character above the average of the studied breeds. In this approach, two economic values were computed. The financial market value of each breed is added to another value related to the private genomic polymorphism. The results showed that the price of the Dman breed would undergo the important increase that is around 3.3 MAD/kg considering that this breed has the largest number of exclusive variants and an important effective population size. Overall, this work may be of interest to policy makers in guiding development programs and projects to encourage breeds that have important adaptation values.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)